2019
DOI: 10.1002/jbt.22292
|View full text |Cite
|
Sign up to set email alerts
|

Crocin inhibits proliferation and induces apoptosis through suppressing MYCN expression in retinoblastoma

Abstract: The pathogenetic mechanisms of retinoblastoma are still not yet fully elucidated, putting limits to efficacious treatment. Crocin is the main component of saffron, which exhibits significant antitumorigenic properties. The aim of this paper is to investigate the effect of crocin on retinoblastoma. The effects of crocin on the proliferation of human retinoblastoma cells were determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, cell number assay, and colony formation assay. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Immunoblot analyses of ADSCs and iSCs after 7 and 19 days of induction were performed with precast gradient gels using standard methods (Deng et al 2019). Briefly, cells were lysed in radioimmunoprecipitation assay (RIPA) buffer and normalized using a BCA protein assay kit (Ther-moFisher Scientific, Carlsbad, CA, USA).…”
Section: Detecting the Effect Of Different Induction Times On Proliferation Senescence And Apoptosis Of Iscsmentioning
confidence: 99%
“…Immunoblot analyses of ADSCs and iSCs after 7 and 19 days of induction were performed with precast gradient gels using standard methods (Deng et al 2019). Briefly, cells were lysed in radioimmunoprecipitation assay (RIPA) buffer and normalized using a BCA protein assay kit (Ther-moFisher Scientific, Carlsbad, CA, USA).…”
Section: Detecting the Effect Of Different Induction Times On Proliferation Senescence And Apoptosis Of Iscsmentioning
confidence: 99%
“…In recent years, many authors studied the effects of different natural compounds on GBM [22]; among these, SE raised great interest. Crocetin is the major active product of SE and has an elevated capacity to counteract the survival and progression of different cancer types [24,[26][27][28]. However, the effects of crocetin on GBM are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Crocin is a natural carotenoid extracted from saffron that is known to have various biological activity including renoprotective (10), anti-oxidant (11), anti-depressant (12) and anti-inflammatory (13) effects. Further, a growing number of papers have confirmed that Crocin also inhibits the progression of multiple cancers (14)(15)(16). Zhou et al reported that Crocin inhibited migration, invasion, and epithelial-mesenchymal transition (EMT) in GC cells (17).…”
Section: Original Articlementioning
confidence: 99%